Effects of Mangosteen Peel Extract Encapsulated By Maltodextrin On Antibacterial Activities of Escherichia coli - Andri Kusmayadi; Lovita Adriani; Abun; Muchtaridi; Ujang Hidayat Tanuwiria (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mangosteen peel extract contains good antibacterial compounds and is thought to be better when microencapsulated is formed. This study aimed to determine the effects of formulation of mangosteen peel ethanol extract associated to maltodextrin on activities of Escherichia coli. It was conducted by disk diffusion method according to Kirby-Bauer test in Mueller Hinton Agar (MHA) using three different concentrations namely: 100, 75, and 50 (%). Each formulation was tested as many as 10 µL disk -1 consisted of each treatment. The employed maltodextrin was obtained by enzymatic processing of arenga starch. Nine formulations were tested by measuring their bacterial inhibition activity in a Mueller Hinton Agar (MHA) medium. The results showed that the effects of formulation between mangosteen peel ethanol extract and maltodextrin had the significant effect (P<0.05) on the antibacterial activities of Escherichia coli. It had been shown the ability to actively inhibit the bacterial growth at medium levels.